2012
DOI: 10.1242/jcs.119552
|View full text |Cite
|
Sign up to set email alerts
|

The function of the M-line protein obscurin in controlling the symmetry of the sarcomere in the flight muscle of Drosophila

Abstract: There was an error published in J. Cell Sci. 125, 3367-3379.In the section 'Effect of reduced obscurin expression on other proteins in IFM', the second sentence was published omitting the term 'M-line'. The correct sentence should read as follows:In wild-type myofibrils, zormin was in both Z-disc and M-line (supplementary material Fig. S3A).On p.3373, left column, second paragraph, second line, the word 'line' was published twice.We apologise for these mistakes. 4170Erratum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…We wanted to verify our surprising finding that N- and C We hypothesized that the small central gap visible in the Proj-kinase domain nanobody patterns is caused by a Projectin-free M-band of the larval sarcomere. Co-labelling the M-band with Obscurin-GFP, which specifically localises to the M-band (Katzemich et al, 2012;Sarov et al, 2016), confirmed that the gap present in the Proj-kinase nanobody pattern is consistent with its absence from the M-band (Figure 7D). Taken together, our results demonstrate that Projectin decorates the myosin filament in a defined polar orientation, likely from the tip of the myosin filament until the beginning of the H-zone that is devoid of myosin heads.…”
Section: Projectin Is Oriented On the Thick Filamentsupporting
confidence: 61%
See 1 more Smart Citation
“…We wanted to verify our surprising finding that N- and C We hypothesized that the small central gap visible in the Proj-kinase domain nanobody patterns is caused by a Projectin-free M-band of the larval sarcomere. Co-labelling the M-band with Obscurin-GFP, which specifically localises to the M-band (Katzemich et al, 2012;Sarov et al, 2016), confirmed that the gap present in the Proj-kinase nanobody pattern is consistent with its absence from the M-band (Figure 7D). Taken together, our results demonstrate that Projectin decorates the myosin filament in a defined polar orientation, likely from the tip of the myosin filament until the beginning of the H-zone that is devoid of myosin heads.…”
Section: Projectin Is Oriented On the Thick Filamentsupporting
confidence: 61%
“…As muscle and in particular sarcomere architecture is well-conserved, Drosophila is a fantastic model to study how a sarcomere is built during development (Katzemich et al, 2013; 2015; Orfanos et al, 2015; Weitkunat et al, 2017; 2014). Generation of monoclonal antibodies against Drosophila sarcomere proteins have been insightful to locate key proteins within the mature sarcomere (Burkart et al, 2007; Ferguson et al, 1994; Katzemich et al, 2012; Lakey et al, 1990; Qiu et al, 2005; Szikora et al, 2020). However, a systematic toolbox of antibodies recognising defined domains of the often large sarcomeric proteins, in particular against defined domains of the two large Drosophila titin homologs Sallimus (Sls) and Projectin (gene called bent, bt ) is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of Unc ‐ 89 using P‐element insertion results in flightless adults in D . melanogaster (Katzemich et al, 2012). Upregulation of these genes in Y M males at lower temperatures might improve muscle performance.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac isoform of myosin-binding protein C (MyBP-C), encoded by MYBPC3, binds to titin (encoded by TTN) and light meromyosin (LMM, the tail region of myosin) in the A-band via its C-terminal domain [8,9]. In the M-band, the myomesin family, namely, myomesin, M-protein/myomesin-2 and myomesin-3, encoded by MYOM1, MYOM2 and MYOM3, respectively in humans [10][11][12], acts as a structural sarcomere stabilizer by cross-connecting thick filaments [13][14][15].…”
Section: (A) Thick Filamentmentioning
confidence: 99%